Contribution of CARD9 signaling to wound healing in skin promoted by topical administration of heat-killed Enterococcus faecalis strain KH2 and the involvement of Dectin-2 - Kurosaka, Shiho; Tanno, Hiromasa; Hirose, Minako; Kamada, Wakana; Takayashiki, Rena; Sone, Ikue; Sato, Yuki; Watanabe, Takumi; Ishi, Shinyo; Shoji, Miki; Imai, Yoshimichi; Sato, Ko; et al. (Frontiers in Immunology, 2025)
IntroductionLactic acid bacteria (LAB) are well known for their beneficial effects on the regulation of immune responses and host protection against microbial infections. We previously reported that heat-killed Enterococcus faecalis strain KH2 (heat-killed KH2), a species of LAB, enhances inflammatory responses at wound sites and accelerates the skin wound healing process. In this study, we aimed to clarify the pathway underlying the wound-healing effects of heat-killed KH2. We focused on CARD9, a common adaptor molecule for C-type lectin receptors and Dectin-2, the upstream receptor for this adaptor molecule.MethodsFour full-thickness dermal wounds were created on the backs of wild-type (WT) mice, CARD9 KO mice, and Dectin-2 KO mice, and the effects of heat-killed KH2 administration were examined. We analyzed the percent wound closure, re-epithelialization, granulation tissue formation, and the production of inflammatory cytokines and chemokines.ResultsHeat-killed KH2 administration enhanced wound closure, granulation tissue formation, and re-epithelialization in WT mice. However, these effects were absent in heat-killed KH2-treated CARD9 KO mice. Similar results were observed in the migration of neutrophils and the production of TNF-α, IL-6, KC, and MIP-2 in heat-killed KH2-treated CARD9 KO mice. Furthermore, heat-killed KH-2 induced activation of reporter cells expressing Dectin-2. Finally, heat-killed KH-2 treatment in Dectin-2 KO mice did not promote skin wound healing.ConclusionThese results suggest that recognition of heat-killed KH2 by Dectin-2 may activate CARD9-mediated signaling, which may contribute to the promotion of skin wound healing through KH2 treatment.